Effects of gamma radiation on the reproductive organs in the red flour beetle Tribolium castaneum (Herbst) - Banu, PA; Ali, IA; Salam, MA (University Journal of Zoology, Rajshahi University, 2007)
Gamma radiation effects on the gonads of Tribolium castaneum were assessed by cytological techniques. Pupal treatments of 15 Gy resulted in the significant reduction of testes and ovaries leading to sterility in males and infecundity in females, respectively. The present findings thus provide an important information for designing a sterile male technique for this storage pest species.Key words: Gamma radiation, Tribolium castaneum, reproductive organsUniv. j. zool. Rajshahi Univ. Vol.25 2006 p.11-14